Editorial Volume 39(1) 2018 - Lessa, Angela B. Cavenaghi T.; Tanzi Neto, Adolfo; Oliveira, Grassinete C. de Albuquerque; Cavalcante, Antonio Bruno Ferreira (The ESPecialist, 2018)
Editorial Volume 39.1 - 2018